Molecular Detection of Virulence Genes (spy1258, scpA, sdaB) and Their Association with Clinical Features of Streptococcus pyogenes Isolated from Pharyngitis Patients (Tikrit Journal of Pharmaceutical Sciences, 2026)
Background: Streptococcus pyogenes is a significant human pathogen responsible for a wide range of diseases.      Objective: This study aimed to identify S. pyogenes isolates from patients with pharyngitis and to investigate their antibiotic resistance profiles and the presence of key virulence genes (scpA, sdaB, and spy1258) using molecular techniques.Methods: A total of 150 throat swabs were collected from pharyngitis patients attending Tikrit Teaching Hospital, Salah Al-Din General Hospital, and private clinics between January and July 2023. Samples underwent bacteriological identification and biochemical testing for S. pyogenes, with confirmation using the VITEK 2 system. Antibiotic susceptibility testing was conducted, and multidrug-resistant isolates were further analyzed by PCR to detect the presence of virulence genesResults: Out of 150 collected samples, 122 isolates were identified as Gram-positive bacteria. Among them, 52 isolates (42.6%) were confirmed as S. pyogenes. Antibiotic susceptibility testing showed variable resistance patterns, with four isolates (7.7%) displaying complete resistance to all tested antibiotics. Molecular analysis revealed the presence of the spy1258 gene in three isolates (5.7%), while scpA and sdaB were each detected in one isolate.                                                                                                           Conclusion: The findings highlight the clinical importance of integrating molecular surveillance of virulence factors and antibiotic resistance in S. pyogenes diagnostics. Routine molecular monitoring can improve early detection, guide effective treatment strategies, and help limit the spread of multidrug-resistant strains within the community.